OPTIMIZATION OF THE MANAGEMENT OF MAINTENANCE OF EDUCATIONAL FACILITIES AND INFRASTRUCTURE TO IMPROVE THE QUALITY OF LEARNING - Mardiana, Dinny; Sujani, Asep; Ruhyat, Alpa; Meilani, Mila; Hetiawati, Ruri C. (Yayasan Education and Social Center, 2025)
This study aims to analyze the optimization of educational facilities and infrastructure maintenance management and its contribution to improving learning quality in secondary schools. Qualitative research with multi-site case study design was conducted in eight junior and senior high schools in Cianjur City, West Java, involving 85 participants consisting of school principals, vice principals for facilities and infrastructure, teachers, school committee members, educational staff, and students. Data were collected through in-depth interviews, participatory observation, and documentation study over four months, then analyzed using Miles, Huberman, and Saldaña thematic approach with NVivo 12. The findings identified four key dimensions of optimization: (1) data-based maintenance planning with priority scales; (2) structured implementation of preventive, corrective, and predictive maintenance; (3) budget allocation of minimum 15-20% of operational budget; (4) continuous monitoring and evaluation. Schools with optimal maintenance systems demonstrated learning quality improvement through smooth learning process (93%), increased student motivation (87%), effective learning media use (89%), minimized disruptions (91%), and higher learning outcomes (average 8.5 points higher). Optimization success was influenced by principal leadership, human resource competence, integrated management systems, stakeholder participation, and organizational culture. The study concludes that optimization of facilities and infrastructure maintenance management contributes significantly to learning quality improvement, recommending development of digital inventory systems, increased budget allocation, implementation of integrated systems, and establishment of minimum maintenance standards in educational policies.